EFL learners' learning involvement and emotions in the integration of technology in their classrooms - Lin, Yang; Yang, Lei; Ergun, Anna Lia Proietti (UNIV GRANADA, 2025)
It is generally believed that technological infrastructures and teachers' and learners' technology literacy are the main prerequisites for conducting a technology-integrated learning environment. However, empirical evidence in the literature demonstrated that language learners might pursue emotive relief in their technology-integrated educational environments to assuage undesirable feelings. Therefore, the current study investigated the relationship between the integration of technology in English as a foreign language (EFL) learners' classrooms, engagement, and emotions. Drawing upon positive psychology, the specified hypotheses were tested by administering three questionnaires among 1,041 EFL learners in Chinese Universities. The results of the study proposed that about 70 percent of changes in the EFL learners' perceptions of technology integration can be predicted by their engagement and emotions. Furthermore, in contrast to prior studies, the association between emotions and learners' perceptions of technology integration was higher in this research. The discoveries highlighted the requirement for a better understanding of the system and that students' engagement and their emotions influence their perceptions of technology integration positively. Lastly, relevant implications for language education are discussed.
Keywords: learning engagement; technology integration; learners' emotions; positive psy-chology; technology-integrated environment; Education & Educational Research; Linguistics